2022
DOI: 10.1186/s12873-022-00659-9
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction among non-conveyed patients and significant others when discharged at the scene by the ambulance service: an exploratory cross-sectional survey

Abstract: Background The ambulance service is facing an increased number of calls and ambulance assignments. Between 12 and 42% of all assignments result in non-conveyance to the Accident and Emergency Department. However, there is limited knowledge regarding satisfaction among patients and significant others when patients are assessed as non-urgent and discharged at the scene. Therefore, the aim of the study was to explore and compare satisfaction with the ambulance service among patients and significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…However, most of the non-conveyed patients in our study thought that the service they received helped them, and the overall evaluations were good. These results are in accordance with previous Swedish, Australian and Finnish studies [ 12 , 14 , 21 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, most of the non-conveyed patients in our study thought that the service they received helped them, and the overall evaluations were good. These results are in accordance with previous Swedish, Australian and Finnish studies [ 12 , 14 , 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, providing self-care instructions or directing the patient to their own general practitioner made patients feel more confident about non-conveyance [ 11 ]. However, there is a difference in study results on whether the family members are less satisfied than the patients themselves [ 12 , 14 ]. Another recent study from Sweden revealed that patients’ experiences of non-conveyance are versatile and complex, as they felt, for example, insecurity and uncertainty [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study's findings supplement the limitations of prehospital emergency care in Africa that contribute to emergency center mortality. This result of users' satisfaction considerably contradicts the majority of studies conducted regarding ambulance service satisfaction that produced a ceiling effect stating a high ambulance service user satisfaction portfolio [3,4,8,10,11,[22][23][24][25][26]. This discrepancy in satisfaction level might be due to the difference in ambulance service quality that exists among developed and developing countries, given that almost all the literature referenced was conducted in well-developed countries and there is a literature gap regarding ambulance service satisfaction in developing countries to compare to.…”
Section: Discussionmentioning
confidence: 82%
“…Their wishes were possibly affected by previous experiences and the sense of severity of an acute situation (63,104,152). Of the older patients who remained at home after assessment by ambulance personnel, most of them were satisfied with the decision (80), among patients of all ages have both satisfaction (153) and dissatisfaction (154) been identified. It is reasonable to assume that older patients also had experienced dissatisfaction.…”
Section: Older Patientsmentioning
confidence: 99%